FAKTOR-FAKTOR YANG MEMPENGARUHI NON PERFORMING LOAN PADA BANK DI INDONESIA - Muhammad Zaenuddin (JOURNAL OF APPLIED MANAGERIAL ACCOUNTING, 2023)
This study aims to examine the effect of return on asset, size, operating expense operating income, solvency ratio, and loan to depostio ratio on non performing loan of bank companies listed on the Indonesia Stock Exchang (IDX) for period 2013-2017. This study uses secondary data with a purposive sampling technique. The sample used in this research is 40 companies with a total observation of 200 data. The analysis technique used is panel data regression analysis. The results of the research found that size had a positive effect on non performing loan, operating expense operating income had a positive effect on non performing loan, return on asset had no effect on non performing loan, solvency ratio had no effect on non performing loan, and loan to deposit ratio had no effect on non performing loan